Different Therapeutic Paths (Colchicine vs. Anakinra) in Two Patients With Schnitzler’s Syndrome - Marko BAREŠIĆ; Joško MITROVIĆ; Jadranka MOROVIĆ VERGLES; Branimir ANIĆ (Archives of Rheumatology, 2016)
Schnitzler’s syndrome is a rare autoinflammatory syndrome with unidentified mechanism of disease and etiology with unknown definitive treatment algorithm. The two obligatory criteria for the diagnosis of Schnitzler’s syndrome include chronic urticarial rash and monoclonal gammopathy (immunoglobulin M or immunoglobulin G). In this article, we describe two patients with different courses of disease with different average lengths of time between initial symptoms and the final diagnosis (6 months to 8 years). Exclusion of more common conditions is needed to ensure the correct diagnosis. Treatment strategy depends on the patient’s constitutional symptoms (fever, malaise, generalized myalgia, and arthralgias) and laboratory tests of inflammation. Treatment includes usage of conventional drugs and cytokine blockade (interleukin-1 and interleukin-6). Further studies are needed to determine the precise mechanism of disease and the appropriate targeted therapy.